Fpk1/2 kinases regulate cellular sphingoid long‐chain base abundance and alter cellular resistance to LCB elevation or depletion. Issue 2 (10th February 2014) - Yamane‐Sando, Yukari; Shimobayashi, Etsuko; Shimobayashi, Mitsugu; Kozutsumi, Yasunori; Oka, Shogo; Takematsu, Hiromu
Abstract Sphingolipids are a family of eukaryotic lipids biosynthesized from sphingoid long‐chain bases (LCBs). Sphingolipids are an essential class of lipids, as their depletion results in cell death. However, acute LCB supplementation is also toxic; thus, proper cellular LCB levels should be maintained. To characterize the "sphingolipid‐signaling intercross, " we performed a kinome screening assay in which budding yeast protein kinase‐knockout strains were screened for resistance to ISP‐1, a potent inhibitor of LCB biosynthesis. Here, one pair of such DIR (deletion‐mediated ISP‐1 resistance) genes, FPK1 and FPK2, was further characterized. Cellular LCB levels increased in the fpk1/2∆ strain, which was hypersensitive to phytosphingosine (PHS), a major LCB species of yeast cells. Concomitantly, this strain acquired resistance to ISP‐1. Fpk1 and Fpk2 were involved in two downstream events; that is, ISP‐1 uptake due to aminophospholipid flippase and LCB degradation due to LCB4 expression. RSK3, which belongs to the p90‐S6K subfamily, was identified as a functional counterpart of Fpk1/2 in mammalian cells as the RSK3 gene functionally complemented the ISP‐1‐resistant phenotype of fpk1/2∆ cells.